The crucial role of cardiac MRI parameters in the prediction of outcomes in acute clinically suspected myocarditis: A functional and feature-tracking study - Motevalli, Marzieh; Asadian, Sanaz; Khademi, Foroogh; Rezaeian, Nahid; Shayan, Leila (Frontiers in Cardiovascular Medicine, 2022)
Background: The definitive diagnosis of myocarditis is made by endomyocardial biopsy, but it is an aggressive method. Recent investigations have proposed that cardiac MRI parameters have both diagnostic and prognostic roles in assessing myocarditis. We aimed to evaluate the role of functional and feature-tracking (FT)-derived strain values in predicting major adverse cardiovascular events (MACE) in patients with acute myocarditis. Methods and Results: We evaluated 133 patients with acute myocarditis (74.4% men) between January 2016 and February 2021. During a mean follow-up of 31±16 months, sixteen patients (12.03%) experienced MACE: 3 deaths (2.3%), 9 ICD implantations (6.9%), and 5 cardiac transplantations (3.8%). The left ventricular ejection fraction (LVEF), the LV end-diastolic volume index (EDVI), and the LV global longitudinal strain (GLS) were the strongest predictors of MACE. Each 1-unit decline in LVEF and LVGLS or 1-unit rise in LVEDVI resulted in a 5%, 24%, and 2% increase in MACE, respectively. LVEF≤36.46% and LVGLS≤9% indicated MACE with 75% sensitivity and 74.4% and 73.5% specificity, respectively. Conclusions: In a group of acute myocarditis patients with evidence of myocardial edema and fibrosis, LVEF and GLS were the strongest predictors of adverse cardiac events.